Comprehensive genome analysis of Mycobacterium avium subsp. paratuberculosis in camels from Saudi Arabia: Molecular epidemiology and antimicrobial resistance - A. Zaghawa; F. Housawi; Ahmed Elsify; Mohamed E. Hasan; Alyaa Elrashedy; Kazem AlMohammed Salem; Nidhal Ben Amor; A. Al Naeem (Veterinary World)
Background and Aim: Paratuberculosis, caused by Mycobacterium avium subsp. paratuberculosis (MAP), is a significant infectious disease affecting livestock, including camels in Saudi Arabia, leading to severe economic losses. Despite its impact, limited genomic studies have been conducted to characterize MAP strains in camels and their antimicrobial resistance (AMR) profiles. This study aimed to (1) characterize the clinical and pathological findings of MAP infections in camels; (2) determine the seroprevalence of MAP in the eastern region of Saudi Arabia; (3) differentiate between MAP strains using polymerase chain reaction (PCR) and bioinformatics tools; (4) conduct a comprehensive genomic analysis; and (5) identify genes associated with AMR, virulence, and immune response.